2018
DOI: 10.1177/0886109917747615
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Pay Equity, and Pay in Social Work and Other Professions

Abstract: Does the social work labor force reflect the field's commitment to social and economic justice? Using individual-level census data for 1980-2014 on self-identified social workers and on other college graduates in college-majority occupations, this article finds three key patterns. First, representation of women, blacks, and Latinx in social work is high and growing, greatly exceeding that in most of these other occupations. Second, white men continue to earn more than comparable women, blacks, and Latinx, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…Social workers who participated in this research were older, with 57.9% (n = 81) reported to be aged 50 and over and most of them were female (93.6%, n = 131). The age group and high percentage of female participants also mirrored the aging workforce and a "female-dominated profession" found in other social work studies (Lewis, 2018;Yeung, Mooney, English, & O'Donohue, 2020). Most of the respondents identified themselves as New Zealand European/ Pākehā (75.0%, n = 105).…”
Section: Resultssupporting
confidence: 58%
“…Social workers who participated in this research were older, with 57.9% (n = 81) reported to be aged 50 and over and most of them were female (93.6%, n = 131). The age group and high percentage of female participants also mirrored the aging workforce and a "female-dominated profession" found in other social work studies (Lewis, 2018;Yeung, Mooney, English, & O'Donohue, 2020). Most of the respondents identified themselves as New Zealand European/ Pākehā (75.0%, n = 105).…”
Section: Resultssupporting
confidence: 58%
“…The example of computer programming -in its infancy a female-typed professiondemonstrates that increasing the social status of a profession can be associated with the marginalization of women in this profession (Ensmenger, 2010). Moreover, research suggests that the positive outcomes of increasing the number of men in femaletyped professions are limited to men who receive higher pay compared to women (Budig, 2002;Lewis, 2018). In addition, in interview studies, men in female-dominated professions reported having some advantages that helped them progress more effectively up the career ladder than their female colleagues (Williams, 1992(Williams, , 2013Simpson, 2004).…”
Section: The Impact Of Women Quotas Vs Men Quotasmentioning
confidence: 99%
“…Some studies rely on internal or nationally representative surveys, which are particularly effective in detecting industry-wide salary biases. For example, several recent studies have used data from the decennial U.S. Census or annual American Community Surveys to examine wage gaps based on both gender and race in the public sector (e.g., Lewis, 2018; Lewis, Pathak, & Galloway, 2018). Several studies used nationally representative surveys of specific populations such as the U.S. National Study of Postsecondary Faculty (Barbezat, 2004; Renzulli et al, 2013), the U.K. National Health Service Survey of Nursing (Pudney & Shields, 2000), or the U.S. Survey of Doctorate Recipients (Ginther, 2004; Ginther & Hayes, 2003; Webber & González Canché, 2015).…”
Section: Salary Studies In the Literaturementioning
confidence: 99%